Role of Cardiovascular Magnetic Resonance to Assess Cardiovascular Inflammation - Filomena, Domenico; Dresselaers, Tom; Bogaert, Jan (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular inflammatory diseases still represent a challenge for physicians. Inflammatory cardiomyopathy, pericarditis, and large vessels vasculitis can clinically mimic a wide spectrum of diseases. While the underlying etiologies are varied, the common physio-pathological process is characterized by vasodilation, exudation, leukocytes infiltration, cell damage, and fibrosis. Cardiovascular magnetic resonance (CMR) allows the visualization of some of these diagnostic targets. CMR provides not only morphological and functional assessment but also tissue catheterization revealing edema, hyperemia, tissue injury, and reparative fibrosis through T2 weighted images, early and late gadolinium enhancement, and parametric mapping techniques. Recent developments showed the role of CMR in the identification of ongoing inflammation also in other CV diseases like myocardial infarction, atherosclerosis, arrhythmogenic and hypertrophic cardiomyopathy. Future developments of CMR, aiming at the specific assessment of immune cell infiltration, will give deeper insight into cardiovascular inflammatory diseases.